Kinerja Aparatur Sipil Negara Pada Dinas Sosial dan Pemberayan Masyarakat Kota Gorontalo - Adam, Sry Fidyawati; Aneta, Asna; Sulila, Ismet (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to find out (1) How the state civil apparatus performs in the social service and community empowerment of Gorontalo City, and (2) What factors determine the performance of the state civil apparatus in the Gorontalo City social and community empowerment service seen from several aspects ( a) Motivation Factor, (b) Ability Factor. This research method is descriptive research using a qualitative approach. The research results show that the performance of the State Civil Apparatus in the Gorontalo City Social and Community Empowerment Service is not yet optimal in terms of quality, quantity, implementation of duties and responsibilities. Quality of work that has not reached the desired standard, quantity of work that has not reached work targets due to differences between existing regulations and the situation in the field, lack of experience in carrying out tasks that are not optimal, lack of awareness about increasing initiative and concern in carrying out tasks causes responsibility does not reach the desired level. The factors that determine the performance of state civil servants in the Gorontalo City Social and Community Empowerment Service are motivation and ability. In this case, there are several state civil servants who depend on other people and lack the ability to manage risks in carrying out their work.